2007
DOI: 10.3748/wjg.v13.i10.1541
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mutant type-p53 products inH pylori-associated chronic gastritis

Abstract: AIM:To investigate the mutation of p 53 immunohistochemically in non-tumorous gastric mucosa with H pylori infection before and after H pylori eradication therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
4
16
2
Order By: Relevance
“…The present study shows the highest frequency of p53 mutation in the groups with H pylori infection, especially among the cagA+ cases, corroborating previous studies [16,3,4] . The high percentage of p53 mutation in EBV-associated and EBV-negative gastric carcinomas was observed in our study which was also demonstrated in other studies, demonstrating that the p53 mutation is a relevant alteration in gastric carcinogenesis independent of the infection [15,16,43] . Finally, this study shows the high prevalence of H pylori infection in gastric carcinomas in Ceará State.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study shows the highest frequency of p53 mutation in the groups with H pylori infection, especially among the cagA+ cases, corroborating previous studies [16,3,4] . The high percentage of p53 mutation in EBV-associated and EBV-negative gastric carcinomas was observed in our study which was also demonstrated in other studies, demonstrating that the p53 mutation is a relevant alteration in gastric carcinogenesis independent of the infection [15,16,43] . Finally, this study shows the high prevalence of H pylori infection in gastric carcinomas in Ceará State.…”
Section: Discussionsupporting
confidence: 90%
“…Kodama et al [43] have suggested an accumulation of wild-type p53, especially in the H pylori infected mucosa probably due to the H pylori-induced DNA damage. The present study shows the highest frequency of p53 mutation in the groups with H pylori infection, especially among the cagA+ cases, corroborating previous studies [16,3,4] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that over-expression of p53 protein detected by immunohistochemistry generally represents mutant p53 (Nardone et al 1999;Murakami et al 1999;Kodama et al 2007), suggesting that the immunochistochemical accumulation of p53 is an indicator of the loss of the p53 tumor suppressor function. Therefore, the p53 protein accumulation detected in non-acid-secreting areas might represent important molecular events involved in the persistent gastric carcinogenesis after H. pylori eradication.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that immunohistochemical accumulation of p53 was found in gastric mucosa infected with H. pylori infection and that it significantly decreased after eradication (Jones et al 1997;Nardone et al 1999;Satoh et al 2001;Kodama et al 2007). On the other hand, another study pointed out that significantly higher accumulation of p53 was detected in the gastric mucosa of patients with multifocal atrophic gastritis 1 year after eradication compared with that of patients with non-atrophic superficial gastritis (Guarner et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the detection of p53 in the presence of lowgrade dysplasia is a risk factor for progression to highgrade dysplasia or cancer. Thus it is expected that p53 mutation status causes the mutant type of p53 expression [19,20]. However, no correlation was found between p53 mutation analysis and immunohistochemical staining in H. pylori-associated gastroduodenal diseases including GC.…”
mentioning
confidence: 99%